Boron-containing and nitrogen-containing carbide and preparation method thereof
By introducing nitrogen elements into high-entropy boron-containing carbides and using pressure-free discharge plasma sintering and high-temperature heat treatment, a single phase solid solution is formed, which solves the defects caused by boron oxidation during the oxidation and ablation process of high-entropy boron-containing carbides, and significantly improves its ablation resistance and oxidation resistance.
Patent Information
- Application Number
- CN202311180019.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-13
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-09-13
AI Technical Summary
During the oxidation and ablation process of high-entropy boron-containing carbide ultra-high temperature ceramic powder, boron will oxidize to form boron oxide, resulting in pores and crack defects, affecting its ablation resistance.
By introducing nitrogen elements into high-entropy boron-containing carbides, a specific preparation method is adopted, including mixing the metal powder with carbon powder and performing pressure-free discharge plasma sintering, and then high-temperature heat treatment with B2O3 powder and g-C3N4 powder under vacuum conditions to form a single phase solid solution with a face-centered cubic structure.
The preparation of a single phase solid solution with high entropy boron and nitrogen carbides is achieved, and the face-centered cubic structure of the carbides is maintained, which significantly improves its ablation resistance and oxidation resistance.
Smart Images

Figure CN119613120A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high-entropy ultrahigh temperature carbide ceramics, and in particular to boron- and nitrogen-containing carbide and a preparation method thereof. Background Art
[0002] Ultra-high temperature ceramics have the advantages of high melting point, high stability and high high temperature strength. They can be used in components such as nose cones and wing leading edges of hypersonic vehicles, throat linings and diffusion sections of rockets, and are important candidate materials for thermal protection systems of space shuttles and strategic missiles. According to the size of the entropy value (S), ultra-high temperature ceramics are usually divided into low entropy ultra-high temperature ceramics (S≤1.0R), medium entropy ultra-high temperature ceramics (1.0R ≤S≤1.5R) and high entropy ultra-high temperature ceramics (S≤1.5R) ceramics, where R is the gas constant.
[0003] High entropy ultra-high temperature ceramics usually refer to solid solutions formed by five or more ceramic components. Due to its novel "high entropy effect" and excellent performance, it has become one of the research hotspots in the ceramic field in recent years. CN109180188A discloses a high entropy boron carbide ultra-high temperature ceramic powder with a molecular formula of XC y B z , wherein X is at least two of Zr, Ti, Hf, V, Nb, Ta, Cr, Mo or W, 0.6≤y<1.0, 0<z≤0.4, y+z=1, and has a single-phase face-centered cubic structure. The ceramic powder is a single-phase solid solution, has a face-centered cubic structure and contains boron, has both the high-temperature resistance of carbides and the anti-oxidation properties of borides, and can be used to prepare high-entropy boron-containing carbide ultra-high temperature ceramic blocks or composite materials that are resistant to ablation and oxidation. However, during the oxidation and ablation process of the boron-containing carbide, boron will oxidize to form boron oxide. When the temperature is higher than its boiling point (1860℃), a large amount of boron oxide will volatilize, causing defects such as pores and cracks, which is not conducive to the ablation resistance of the boron-containing carbide. Therefore, the ablation resistance of high-entropy boron-containing carbide ceramics still needs to be further improved.
[0004] Wen et al. synthesized a carbide solid solution containing N and C (Hf 0.2 Zr 0.2 Ta 0.2 Nb 0.2 Ti 0.2 )(C 0.5 N 0.5 )(WenT, et al. Journal of the American Ceramic Society, 2020, 103(11): 6475-6489), Peng et al. synthesized (Hf 0.2 Zr 0.2 Ta 0.2 Nb0.2 Ti 0.2 )(C 0.8 N 0.2 ) (Peng Z, et al. CorrosionScience, 2021, 184: 109359). Their research results show that N doping enables carbide ceramics to form stronger chemical bonds, giving them higher ablation resistance.
[0005] The introduction of nitrogen into high-entropy boron-containing carbide ultra-high temperature ceramic powder can improve the ablation resistance. However, the introduction of N elements easily leads to the formation of new phases. At present, there are no reports on the preparation method of single-phase boron-containing nitrogen-containing high-entropy carbide ceramics. This is because the reaction free energy of N element with metal elements in the IV and V subgroups of the periodic table is lower. Compared with C and B elements, it will preferentially form stable nitrides, making it difficult for C and B elements to further dissolve into carbides, and then the introduced C and B elements do not dissolve but react with metal elements to form a second phase.
[0006] Guan et al. (GUAN J, et al. Journal of the American Ceramic Society, 2022, 105(10): 6417-6426) mixed various metal powders and amorphous BCN powders by high-energy ball milling and hot-pressed sintering at 1900°C to produce boron-nitrogen-containing carbide composite ceramics. However, the boron-nitrogen-containing carbide composite ceramics have multiple phases, including BN(C) phase, (Ta 0.2 Nb 0.2 Zr 0.2 Hf 0.2 Ti 0.2 )(B,C,N) phase and oxide phase, and as the amount of BCN added decreases, a new phase MB2 appears. This document does not involve how to prepare only (Ta 0.2 Nb 0.2 Zr 0.2 Hf 0.2 Ti 0.2 )(B,C,N) phase correlation method.
[0007] Therefore, there is an urgent need to provide a boron- and nitrogen-containing carbide having a single phase, which does not destroy the face-centered cubic structure of the carbide and contains both boron and nitrogen elements, and a preparation method thereof. Summary of the invention
[0008] The purpose of the present invention is to solve the problem that high entropy boron-containing carbide ultra-high temperature ceramic powder has poor ablation resistance, and to provide a boron-containing and nitrogen-containing carbide and a preparation method thereof.
[0009] In order to achieve the above object, the first aspect of the present invention provides a boron-containing nitrogen-containing carbide, wherein the molecular formula of the boron-containing nitrogen-containing carbide is XC y B z N w , wherein X is at least 4 of Zr, Hf, Ti, Ta, Nb, V, and W, 0.6≤y<1, 0<z≤0.4, 0<w≤0.4, y+z+w≤1, and the boron- and nitrogen-containing carbide is a single-phase solid solution having a face-centered cubic structure.
[0010] Preferably, X is four or five of Zr, Hf, Ti, Ta, Nb, V, and W.
[0011] Preferably, X is Zr, Hf, Ti and Ta, or X is Zr, Hf, Ti, Ta and Nb.
[0012] Preferably, 0.75≤y≤0.95, 0.01≤z≤0.15, 0.05≤w≤0.15, y+z+w≤1.
[0013] Preferably, the molecular formula of the boron- and nitrogen-containing carbide is (Zr 0.25 Hf 0.25 Ti 0.25 Ta 0.25 )(C 0.82 B 0.10 N 0.08 )、(Zr 0.4 Hf 0.2 Ti 0.2 Ta 0.2 )(C 0.70 B 0.15 N 0.15 )、(Zr 0.2 Hf 0.2 Ti 0.2 Ta 0.2 Nb 0.2 )(C 0.90 B 0.03 N 0.07 )、(Zr 0.3 Hf 0.3 Ti 0.2 Ta 0.1 Nb 0.1 )(C 0.87 B 0.06 N 0.07 )
[0014] A second aspect of the present invention provides a method for preparing a boron- and nitrogen-containing carbide, wherein the method comprises the following steps: (1) mixing metal powder and carbon powder and grinding them to obtain a mixed powder; wherein the metal powder is at least four selected from the group consisting of Zr powder, Hf powder, Ti powder, Ta powder, Nb powder, V powder, and W powder; (2) subjecting the mixed powder to pressureless spark plasma sintering to obtain carbide powder; (3) Mixing the carbide powder and B2O3 powder under vacuum conditions and then calcining to obtain boron-containing carbide powder; (4) Under vacuum conditions, mixing the boron-containing carbide powder with g-C3N4 powder and subjecting the mixture to high-temperature heat treatment to obtain boron-containing and nitrogen-containing carbides; wherein the temperature of the high-temperature heat treatment is 1500-1800°C; Wherein, the molecular formula of the boron- and nitrogen-containing carbide is XC y B z N w , X is metal, 0.6≤y<1, 0<z≤0.4, 0<w≤0.4, y+z+w≤1.
[0015] Preferably, the metal powder is selected from four or five of Zr powder, Hf powder, Ti powder, Ta powder, Nb powder, V powder and W powder.
[0016] Preferably, the metal powder is Zr powder, Hf powder, Ti powder and Ta powder, or the metal powder is Zr powder, Hf powder, Ti powder, Ta powder and Nb powder.
[0017] Preferably, the grinding is wet ball milling; wherein the operating conditions of the wet ball milling include: a ball milling speed of 150-300 rpm, a ball milling time of 1-5 h, a ball milling medium of ethanol and / or water, and a ball-to-material ratio of 6-10:1.
[0018] Preferably, the operating conditions of the pressureless spark plasma sintering include: vacuum degree ≤10Pa, heating rate of 50-150°C / min, temperature of 1300-1800°C, and holding time of 15-60min.
[0019] Preferably, the operating conditions of the pressureless spark plasma sintering include: vacuum degree ≤ 5 Pa, heating rate of 80-120° C. / min, temperature of 1500-1700° C., and holding time of 20-40 min.
[0020] Preferably, the calcination operating conditions include: vacuum degree ≤10Pa, heating rate of 30-150°C / min, temperature of 1400-1900°C, and holding time of 15-60min.
[0021] Preferably, the calcination operating conditions include: vacuum degree ≤ 5 Pa, heating rate of 50-100° C. / min, temperature of 1600-1800° C., and holding time of 20-40 min.
[0022] Preferably, the temperature of the high temperature heat treatment is 1600-1700°C.
[0023] Preferably, the vacuum degree of the high temperature heat treatment is ≤10Pa, preferably ≤5Pa; the heating rate is 30-150°C / min, preferably 50-100°C / min; and the holding time is 15-60min, preferably 20-40min.
[0024] Through the above technical solution, the beneficial technical effects achieved by the present invention are as follows: 1) The boron-nitrogen-containing carbide provided in the present invention contains both B and N elements, has a single phase, has a face-centered cubic structure, and has excellent ablation resistance and oxidation resistance; 2) The method for preparing boron- and nitrogen-containing carbides provided in the present invention has a short preparation time, is easy to control the reaction process, and has no impurities introduced during the process, which is conducive to optimizing the content of each component and obtaining a high-purity single-phase solid solution. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the microscopic morphology and elemental surface scanning analysis diagram of the boron- and nitrogen-containing carbide prepared in Example 1; Figure 2 is the XRD pattern of the boron- and nitrogen-containing carbide prepared in Example 1; Figure 3 is the XRD pattern of the boron- and nitrogen-containing carbide prepared in Comparative Example 1; Figure 4 This is the XRD diagram of the boron-containing carbide prepared in Comparative Example 2. DETAILED DESCRIPTION
[0026] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0027] The first aspect of the present invention provides a boron-containing nitrogen-containing carbide, wherein the molecular formula of the boron-containing nitrogen-containing carbide is XC y B z N w, wherein X is at least 4 of Zr, Hf, Ti, Ta, Nb, V, and W, 0.6≤y<1, 0<z≤0.4, 0<w≤0.4, and y+z+w≤1; the boron- and nitrogen-containing carbide is a single-phase solid solution and has a face-centered cubic structure.
[0028] Among them, in the present invention, the boron-containing and nitrogen-containing carbide contains both B and N elements, has a single phase, has a face-centered cubic structure, and has excellent ablation resistance and oxidation resistance.
[0029] In a preferred embodiment of the present invention, X is 4 or 5 of Zr, Hf, Ti, Ta, Nb, V, and W.
[0030] Among them, in the present invention, Zr, Hf, Ti, Ta, Nb, V, and W can form a solid solution. The present invention has a limit on the number of types of X, but does not specifically limit the composition ratio of various metals in X. For example, X can be Zr, Hf, Ti, and Ta in any proportion, or Zr, Hf, Ti, Ta, and Nb in any proportion. Preferably, the composition of various metals in X is the same.
[0031] In a preferred embodiment of the present invention, y may be 0.6, 0.65, 0.7, 0.75, 0.8, 0.9, 0.95, 0.96, 0.97, 0.98, 0.99, 0.999, and any number therebetween, preferably, 0.75≤y≤0.95.
[0032] In a preferred embodiment of the present invention, z can be 0.001, 0.01, 0.1, 0.12, 0.15, 0.18, 0.2, 0.22, 0.25, 0.28, 0.3, 0.32, 0.35, 0.38, 0.4, and any number between these values, preferably, 0.01≤z≤0.15.
[0033] In a preferred embodiment of the present invention, w can be 0.001, 0.01, 0.1, 0.12, 0.15, 0.18, 0.2, 0.22, 0.25, 0.28, 0.3, 0.32, 0.35, 0.38, 0.4, and any number between these values, preferably, 0.05≤w≤0.15.
[0034] In a preferred embodiment of the present invention, the molecular formula of the boron- and nitrogen-containing carbide is (Zr 0.25 Hf 0.25 Ti 0.25 Ta 0.25 )(C 0.82 B 0.10 N 0.08 )、(Zr0.4 Hf 0.2 Ti 0.2 Ta 0.2 )(C 0.70 B 0.15 N 0.15 )、(Zr 0.2 Hf 0.2 Ti 0.2 Ta 0.2 Nb 0.2 )(C 0.90 B 0.03 N 0.07 )、(Zr 0.3 Hf 0.3 Ti 0.2 Ta 0.1 Nb 0.1 )(C 0.87 B 0.06 N 0.07 ).
[0035] The boron- and nitrogen-containing carbide provided in the present invention has both the ultra-high melting point heat resistance of carbides and nitrides and the anti-oxidation property of borides, and has important potential applications in ultra-high temperature thermal protection systems.
[0036] A second aspect of the present invention provides a method for preparing a boron- and nitrogen-containing carbide, wherein the method comprises the following steps: (1) mixing metal powder and carbon powder and grinding them to obtain a mixed powder; wherein the metal powder is at least four selected from the group consisting of Zr powder, Hf powder, Ti powder, Ta powder, Nb powder, V powder, and W powder; (2) subjecting the mixed powder to pressureless spark plasma sintering to obtain carbide powder; (3) Mixing the carbide powder and B2O3 powder under vacuum conditions and then calcining to obtain boron-containing carbide powder; (4) Under vacuum conditions, mixing the boron-containing carbide powder with g-C3N4 powder and subjecting the mixture to high-temperature heat treatment to obtain boron-containing and nitrogen-containing carbides; wherein the temperature of the high-temperature heat treatment is 1500-1800°C; Wherein, the molecular formula of the boron- and nitrogen-containing carbide is XC y B z N w , X is metal, 0.6≤y<1, 0<z≤0.4, 0<w≤0.4, y+z+w≤1.
[0037] Among them, in the present invention, the C in the g-C3N4 powder is mainly used to react with the O element introduced by the B2O3 powder to eliminate the O element. If there is still g-C3N4 powder left after eliminating the oxygen element, the excess g-C3N4 powder will be dissolved into the boron-containing and nitrogen-containing carbide during the preparation process, but will not form a second phase. Therefore, by adjusting the feeding amount of metal powder, carbon powder, B2O3 powder and g-C3N4 powder, a carbon with a molecular formula of XC can be prepared. y B z N w Boron- and nitrogen-containing carbides.
[0038] In step (1): In a preferred embodiment of the present invention, the metal powder is selected from four or five of Zr powder, Hf powder, Ti powder, Ta powder, Nb powder, V powder and W powder.
[0039] The present invention does not specifically limit the mixing ratio of the metal powders, and the amounts of the various metal powders can be adjusted according to actual needs. Preferably, the amounts of the various metal powders in X are the same.
[0040] In a preferred embodiment of the present invention, the metal powder is Zr powder, Hf powder, Ti powder and Ta powder, or Zr powder, Hf powder, Ti powder, Ta powder and Nb powder.
[0041] In a preferred embodiment of the present invention, the purity of the metal powder and the carbon powder are both ≥98%, and the metal powder and the carbon powder are both micron-scale and / or nano-scale powders.
[0042] In a preferred embodiment of the present invention, the grinding is selected from ball milling, preferably wet ball milling; wherein the operating conditions of the wet ball milling include: ball milling speed of 150-300 rpm, ball milling time of 1-5h, ball milling medium of ethanol and / or water, and ball-to-material ratio of 6-10:1.
[0043] In a preferred embodiment of the present invention, the ball milling is followed by drying to obtain a mixed powder, wherein the drying temperature may be 30-60°C.
[0044] In step (2): In a preferred embodiment of the present invention, the operating conditions of the pressureless spark plasma sintering include: vacuum degree ≤10Pa, preferably ≤5Pa; heating rate 50-150℃ / min, preferably 80-120℃ / min; temperature 1300-1800℃, preferably 1500-1700℃; holding time 15-60min, preferably 20-40min.
[0045] Among them, in the present invention, after mixing metal powder and carbon powder, pressureless spark plasma sintering can be performed to prepare a non-stoichiometric high-purity, low-free carbon content single-phase carbide solid solution powder material with carbon vacancy defects. The formation of carbon vacancy defects can create conditions for the introduction of B elements and N elements.
[0046] In a preferred embodiment of the present invention, after the pressureless spark plasma sintering, the sintered product is crushed and ball-milled to obtain carbide powder.
[0047] Among them, in the present invention, the ball milling after pressureless spark plasma sintering is preferably wet ball milling, and the operating conditions of the wet ball milling include: the ball milling speed is 150-300 rpm, the time is 1-5h, the ball milling medium is ethanol and / or water, and the ball-to-material ratio is 6-10:1.
[0048] In step (3): In a preferred embodiment of the present invention, the purity of the B2O3 powder is ≥98%, and the powder is micron-sized and / or nano-sized.
[0049] In a preferred embodiment of the present invention, the calcination operating conditions include: vacuum degree ≤10Pa, preferably ≤5Pa; heating rate of 30-150℃ / min, preferably 50-100℃ / min; temperature of 1400-1900℃, preferably 1600-1800℃; holding time of 15-60min, preferably 20-40min.
[0050] In step (4): In a preferred embodiment of the present invention, the purity of the g-C3N4 powder is ≥98%, and the powder is micron-sized and / or nano-sized.
[0051] Among them, in the present invention, the inventors have found through research that when g-C3N4 powder is used as a nitrogen source, on the one hand, the C in g-C3N4 can consume the O element introduced by B2O3 powder to avoid the formation of a metal oxide phase; on the other hand, the N element can fill the carbon vacancies in the carbide and dissolve into the carbide lattice to form a solid solution without destroying the face-centered cubic structure of the carbide.
[0052] In a preferred embodiment of the present invention, the temperature of the high temperature heat treatment is preferably 1600-1700°C In a preferred embodiment of the present invention, the vacuum degree of the high temperature heat treatment is ≤10Pa, preferably ≤5Pa; the heating rate is 30-150°C / min, preferably 50-100°C / min; and the holding time is 15-60min, preferably 20-40min.
[0053] Among them, in the present invention, the calcination in step (3) and the high-temperature heat treatment in step (4) can be carried out under vacuum, and there is no special limitation on the heating method and heating equipment. The heating equipment includes but is not limited to vacuum sintering furnace, spark plasma sintering furnace, high-temperature graphitization furnace, muffle furnace and other equipment. Preferably, the calcination in step (3) and the high-temperature heat treatment in step (4) are carried out in a vacuum sintering furnace, and both are pressureless sintering.
[0054] In a preferred embodiment of the present invention, 0.75≤y≤0.95, 0.01≤z≤0.15, 0.05≤w≤0.15, y+z+w≤1.
[0055] The preparation method of boron-containing nitrogen-containing carbides provided in the present invention uses B2O3 powder as the B source and g-C3N4 powder as the N source, which can ensure that there are no impurity elements in the synthesized boron-containing nitrogen-containing carbides and no other phases will be generated. Not only can a high-purity single-phase solid solution be obtained, but the preparation time can also be shortened, the difficulty of controlling the preparation process can be reduced, and it is more conducive to optimizing the design of the content of each component, and significantly improving the ablation resistance and antioxidant properties of the boron-containing nitrogen-containing carbides.
[0056] The present invention will be described in detail below through examples. In the examples and comparative examples, Zr powder, Hf powder, Ti powder, Ta powder, Nd powder, carbon powder, B2O3 powder and g-C3N4 powder are all micron-grade powders with a purity of ≥99%.
[0057] Example 1 (1) Zr powder, Hf powder, Ti powder, Ta powder and C powder were mixed in a molar ratio of 0.25:0.25:0.25:0.25:0.8, and the mixture was ball-milled for 2 h in a planetary ball mill, wherein the ball-milling medium was ethanol, the rotation speed was 200 rpm, and the ball-to-material ratio was 6:1. The mixture was taken out after ball-milling, dried at 40°C, and sieved to obtain a mixed powder; (2) placing the mixed powder in a pressureless spark plasma sintering graphite mold for pressureless spark plasma sintering, with the vacuum degree in the furnace being less than 5 Pa, heating the mixture to 1600°C at a heating rate of 100°C / min and keeping the temperature for 30 min, then cooling the mixture to room temperature, taking it out and breaking it, and grinding it into powder in a ball mill, with ethanol as the ball milling medium, a rotation speed of 200 rpm, a ball-to-material ratio of 6:1, and a ball milling time of 0.5 h. After ball milling, taking it out and drying it at 40°C to obtain carbide powder; (3) Based on the B element in the B2O3 powder and the C element in the carbide powder, the B2O3 powder and the above carbide powder are mixed in ethanol at a molar ratio of 0.1:0.8, taken out after 24 hours, and dried at 40°C; then placed in a graphite pot, and pressurelessly sintered in a vacuum sintering furnace with a vacuum degree of less than 5 Pa, and heated to 1600°C at a heating rate of 50°C / min, kept at this temperature for 30 minutes, and then cooled to room temperature and taken out to obtain boron-containing carbide powder; (4) Based on the N element in the g-C3N4 powder and the C element in the boron-containing carbide powder, the g-C3N4 powder and the boron-containing carbide powder were mixed in deionized water at a molar ratio of 0.1:0.8, taken out after 24 hours, and dried at 40°C; then placed in a graphite pot and pressurelessly sintered in a vacuum sintering furnace with a vacuum degree of less than 5 Pa. The temperature was raised to 1700°C at a heating rate of 50°C / min, kept at this temperature for 30 minutes, and then cooled to room temperature and taken out to obtain boron- and nitrogen-containing carbide powder.
[0058] Figure 1 The microscopic morphology and elemental surface scanning analysis diagram of the boron-containing nitrogen-containing carbide prepared in Example 1. The figure shows that the particle size of the boron-containing nitrogen-containing carbide powder is ~100 nm, and the elemental surface scanning results show that the powder contains Zr, Hf, Ti, Ta, C, B and N elements, and the elements are evenly distributed, indicating that the boron-containing nitrogen-containing carbide powder forms a solid solution.
[0059] According to ICP-OES element content analysis, the atomic ratio of Zr, Hf, Ti and Ta is 0.25:0.25:0.25:0.25, the atomic ratio of C, B and N is 0.82:0.10:0.08, and the molecular formula of the boron-nitrogen-containing carbide powder is (Zr 0.25 Hf 0.25 Ti 0.25 Ta 0.25 )(C 0.82 B 0.10 N 0.08 ).
[0060] Example 2 (1) Zr powder, Hf powder, Ti powder, Ta powder, Nd powder and C powder were mixed in a molar ratio of 0.2:0.2:0.2:0.2:0.2:0.9, and the mixture was ball-milled for 2 h in a planetary ball mill, wherein the ball-milling medium was ethanol, the rotation speed was 150 rpm, and the ball-to-material ratio was 6:1. The mixture was taken out after ball-milling, dried at 40°C, and sieved to obtain a mixed powder; (2) placing the mixed powder in a pressureless spark plasma sintering graphite mold for pressureless spark plasma sintering, with the vacuum degree in the furnace being less than 5 Pa, heating the mixture to 1600°C at a heating rate of 100°C / min and keeping the temperature for 30 min, then cooling the mixture to room temperature, taking it out and breaking it, and grinding it into powder in a ball mill, with ethanol as the ball milling medium, a rotation speed of 200 rpm, a ball-to-material ratio of 6:1, and a ball milling time of 0.5 h. After ball milling, taking it out and drying it at 40°C to obtain carbide powder; (3) Based on the B element in the B2O3 powder and the C element in the carbide powder, the B2O3 powder and the above carbide powder are mixed in ethanol at a molar ratio of 0.1:0.9, taken out after 24 hours, and dried at 40°C; then placed in a graphite pot, and pressurelessly sintered in a vacuum sintering furnace with a vacuum degree of less than 5 Pa, and heated to 1800°C at a heating rate of 100°C / min and kept at this temperature for 30 minutes, then cooled to room temperature and taken out to obtain boron-containing carbide powder; (4) Based on the N element in the g-C3N4 powder and the C element in the boron-containing carbide powder, the g-C3N4 powder and the boron-containing carbide powder were mixed in deionized water at a molar ratio of 0.1:0.9, taken out after 24 hours, and dried at 40°C; then placed in a graphite pot and pressurelessly sintered in a vacuum sintering furnace with a vacuum degree of less than 5 Pa. The temperature was increased to 1600°C at a heating rate of 100°C / min and kept at this temperature for 30 min. Then, the mixture was cooled to room temperature and taken out to obtain boron- and nitrogen-containing carbide powder.
[0061] According to ICP-OES element content analysis, the atomic ratio of Zr, Hf, Ti, Ta and Nb is 0.2:0.2:0.2:0.2:0.2, the atomic ratio of C, B and N is 0.90:0.03:0.70, and the molecular formula of the boron-nitrogen-containing carbide powder is (Zr 0.2 Hf 0.2 Ti 0.2 Ta 0.2 Nb 0.2 )(C 0.90 B 0.03 N 0.07 ).
[0062] Example 3 (1) Zr powder, Hf powder, Ti powder, Ta powder and C powder were mixed in a molar ratio of 0.4:0.2:0.2:0.2:0.7, and ball milled for 2 h in a planetary ball mill, wherein the ball milling medium was ethanol, the rotation speed was 200 rpm, and the ball-to-material ratio was 6:1. After ball milling, the mixture was taken out, dried at 40°C, and sieved to obtain a mixed powder; (2) placing the mixed powder in a pressureless discharge plasma sintering graphite mold for pressureless discharge plasma sintering, with the vacuum degree in the furnace being less than 5 Pa, heating the mixture to 1800°C at a heating rate of 60°C / min and keeping the temperature for 15 min, then cooling the mixture to room temperature, taking it out and crushing it, and grinding it into powder in a ball mill, with ethanol as the ball milling medium, a rotation speed of 200 rpm, a ball-to-material ratio of 6:1, and a ball milling time of 0.5 h. After ball milling, taking it out and drying it at 40°C to obtain carbide powder; (3) Based on the B element in the B2O3 powder and the C element in the carbide powder, the B2O3 powder and the above carbide powder are mixed in ethanol at a molar ratio of 0.15:0.7, taken out after 24 hours, and dried at 40°C; then placed in a graphite pot, and pressurelessly sintered in a vacuum sintering furnace with a vacuum degree of less than 5 Pa, and heated to 1600°C at a heating rate of 30°C / min, kept at this temperature for 15 minutes, and then cooled to room temperature and taken out to obtain boron-containing carbide powder; (4) Based on the N element in the g-C3N4 powder and the C element in the boron-containing carbide powder, the g-C3N4 powder and the boron-containing carbide powder were mixed in deionized water at a molar ratio of 0.15:0.7, taken out after 24 hours, and dried at 40°C; then placed in a graphite pot and pressurelessly sintered in a vacuum sintering furnace with a vacuum degree of less than 5 Pa. The temperature was raised to 1800°C at a heating rate of 120°C / min, kept at this temperature for 15 minutes, and then cooled to room temperature and taken out to obtain boron- and nitrogen-containing carbide powder.
[0063] According to ICP-OES element content analysis, the atomic ratio of Zr, Hf, Ti and Ta is 0.4:0.2:0.2:0.2, the atomic ratio of C, B and N is 0.70:0.15:0.15, and the molecular formula of the boron-nitrogen-containing carbide powder is (Zr 0.4 Hf 0.2 Ti 0.2 Ta 0.2 )(C 0.70 B 0.15 N 0.15 ).
[0064] Example 4 (1) Zr powder, Hf powder, Ti powder, Ta powder, Nd powder and C powder were mixed in a molar ratio of 0.3:0.3:0.1:0.1:0.1:0.9, and the mixture was ball-milled for 2 h in a planetary ball mill, wherein the ball-milling medium was ethanol, the rotation speed was 150 rpm, and the ball-to-material ratio was 6:1. The mixture was taken out after ball-milling, dried at 40°C, and sieved to obtain a mixed powder; (2) placing the mixed powder in a pressureless spark plasma sintering graphite mold for pressureless spark plasma sintering, with the vacuum degree in the furnace being less than 5 Pa, heating the mixture to 1400°C at a heating rate of 140°C / min and keeping the temperature for 50 min, then cooling the mixture to room temperature, taking it out and crushing it, and grinding it into powder in a ball mill, with ethanol as the ball milling medium, a rotation speed of 200 rpm, a ball-to-material ratio of 6:1, and a ball milling time of 0.5 h. After ball milling, taking it out and drying it at 40°C to obtain carbide powder; (3) Based on the B element in the B2O3 powder and the C element in the carbide powder, the B2O3 powder and the above carbide powder are mixed in ethanol at a molar ratio of 0.1:0.9, taken out after 24 hours, and dried at 40°C; then placed in a graphite pot, and pressurelessly sintered in a vacuum sintering furnace with a vacuum degree of less than 5 Pa, and heated to 1500°C at a heating rate of 120°C / min and kept at this temperature for 50 minutes, then cooled to room temperature and taken out to obtain boron-containing carbide powder; (4) Based on the N element in the g-C3N4 powder and the C element in the boron-containing carbide powder, the g-C3N4 powder and the boron-containing carbide powder were mixed in deionized water at a molar ratio of 0.1:0.9, taken out after 24 hours, and dried at 40°C; then placed in a graphite pot, and pressurelessly sintered in a vacuum sintering furnace with a vacuum degree of less than 5 Pa. The temperature was raised to 1500°C at a heating rate of 30°C / min, kept at this temperature for 50 minutes, and then cooled to room temperature and taken out to obtain boron- and nitrogen-containing carbide powder.
[0065] According to ICP-OES element content analysis, the atomic ratio of Zr, Hf, Ti, Ta and Nb is 0.3:0.3:0.2:0.1:0.1, the atomic ratio of C, B and N is 0.87:0.06:0.07, and the molecular formula of the boron-nitrogen-containing carbide powder is (Zr 0.3 Hf 0.3 Ti 0.2 Ta 0.1 Nb 0.1 )(C 0.87 B 0.06 N 0.07 ).
[0066] Comparative Example 1 The same as Example 1, except that in step (4), the vacuum sintering furnace is heated to 1300° C. at a heating rate of 30° C. / min.
[0067] (1) Zr powder, Hf powder, Ti powder, Ta powder and C powder were mixed in a molar ratio of 0.25:0.25:0.25:0.25:0.8, and the mixture was ball-milled for 2 h in a planetary ball mill, wherein the ball-milling medium was ethanol, the rotation speed was 200 rpm, and the ball-to-material ratio was 6:1. The mixture was taken out after ball-milling, dried at 40°C, and sieved to obtain a mixed powder; (2) placing the mixed powder in a pressureless spark plasma sintering graphite mold for pressureless spark plasma sintering, with the vacuum degree in the furnace being less than 5 Pa, heating the mixture to 1600°C at a heating rate of 100°C / min and keeping the temperature for 30 min, then cooling the mixture to room temperature, taking it out and breaking it, and grinding it into powder in a ball mill, with ethanol as the ball milling medium, a rotation speed of 200 rpm, a ball-to-material ratio of 6:1, and a ball milling time of 0.5 h. After ball milling, taking it out and drying it at 40°C to obtain carbide powder; (3) Based on the B element in the B2O3 powder and the C element in the carbide powder, the B2O3 powder and the above carbide powder are mixed in ethanol at a molar ratio of 0.1:0.8, taken out after 24 hours, and dried at 40°C; then placed in a graphite pot, and pressurelessly sintered in a vacuum sintering furnace with a vacuum degree of less than 5 Pa, and heated to 1600°C at a heating rate of 50°C / min, kept at this temperature for 30 minutes, and then cooled to room temperature and taken out to obtain boron-containing carbide powder; (4) Based on the N element in the g-C3N4 powder and the C element in the boron-containing carbide powder, the g-C3N4 powder and the boron-containing carbide powder were mixed in deionized water at a molar ratio of 0.1:0.8, taken out after 24 hours, and dried at 40°C; then placed in a graphite pot and pressurelessly sintered in a vacuum sintering furnace with a vacuum degree of less than 5 Pa. The temperature was raised to 1300°C at a heating rate of 50°C / min, kept at this temperature for 30 minutes, and then cooled to room temperature and taken out to obtain boron- and nitrogen-containing carbide powder.
[0068] Comparative Example 2 The same as Example 1, except that step 4 is omitted and a carbon source is added in step 3.
[0069] (1) Zr powder, Hf powder, Ti powder, Ta powder and C powder were mixed in a molar ratio of 0.25:0.25:0.25:0.25:0.8, and the mixture was ball-milled for 2 h in a planetary ball mill, wherein the ball-milling medium was ethanol, the rotation speed was 200 rpm, and the ball-to-material ratio was 6:1. The mixture was taken out after ball-milling, dried at 40°C, and sieved to obtain a mixed powder; (2) placing the mixed powder in a pressureless discharge plasma sintering graphite mold for pressureless discharge plasma sintering, with the vacuum degree in the furnace being less than 5 Pa, heating the mixture to 1600°C at a heating rate of 100°C / min and keeping the temperature for 30 min, then cooling the mixture to room temperature, taking it out and crushing it, and grinding it into powder in a ball mill, with ethanol as the ball milling medium, a rotation speed of 200 rpm, a ball-to-material ratio of 6:1, and a ball milling time of 0.5 h. After ball milling, taking it out and drying it at 40°C to obtain carbide powder; (3) Based on the B element in the B2O3 powder and the C element in the carbide powder, the B2O3 powder and the above-mentioned carbide powder are mixed in ethanol at a molar ratio of 0.1:0.8, and 6 wt% phenolic resin based on the total mass of the powder is added. After 24 hours, the mixture is taken out and dried at 40°C. Thereafter, the mixture is placed in a graphite pot and pressurelessly sintered in a vacuum sintering furnace with a vacuum degree of less than 5 Pa. The temperature is raised to 1600°C at a heating rate of 50°C / min, and the mixture is kept at this temperature for 30 minutes. The mixture is then cooled to room temperature and taken out to obtain boron-containing carbide powder.
[0070] According to ICP-OES element content analysis, the atomic ratio of Zr, Hf, Ti and Ta is 0.25:0.25:0.25:0.25, the atomic ratio of C, B and N is 0.83:0.10, and the molecular formula of the boron-nitrogen-containing carbide powder is (Zr 0.25 Hf 0.25 Ti 0.25 Ta 0.25 )(C 0.83 B 0.10 ).
[0071] Test Example 1 The powders prepared in Example 1 and Comparative Examples 1-2 were characterized by XRD. The characterization results were as follows: Figure 2-4 shown.
[0072] Figure 2 is the XRD pattern of the boron- and nitrogen-containing carbide powder prepared in Example 1. Figure 2 It can be seen that the single phase solid solution of boron- and nitrogen-containing carbide powder prepared in Example 1 has a face-centered cubic structure.
[0073] Figure 3 is the XRD pattern of the boron- and nitrogen-containing carbide powder prepared in Comparative Example 1. Figure 3It can be seen that the boron-nitrogen-containing carbide powder prepared in Comparative Example 1 shows diffraction peaks of Zr-Hf-Ti-Ta-CBN solid solution, HfO2 and g-C3N4, indicating that the powder is a mixture of these three substances. Among them, the Zr-Hf-Ti-Ta-CBN solid solution shows the characteristic peak of ZrC, indicating that when the high-temperature heat treatment temperature is low, the reaction of g-C3N4 and O introduced by B2O3 is incomplete, and the final powder contains oxide impurities HfO2, and the powder cannot form a single phase of boron-nitrogen-containing carbide.
[0074] Figure 4 is the XRD pattern of the boron carbide powder prepared in Comparative Example 2. Figure 4 It can be seen that the boron carbide powder is a single phase solid solution with a face-centered cubic structure.
[0075] Test Example 2 The products prepared in Example 1 and Comparative Example 2 were tested for ablation performance and anti-oxidation performance. The test results are shown in Table 1: The boron-nitrogen-containing carbide powder prepared in Example 1 and the boron-containing carbide powder prepared in Comparative Example 2 were heated to 1900°C at 100°C / min under vacuum conditions (<5 Pa), and maintained at 50 MPa for 10 min to obtain bulk ceramics with a relative density of >95%. The bulk ceramics were tested for ablation performance in a plasma ablation device, and the mass ablation rate / % was calculated based on the mass change of the ceramics before and after ablation. The ablation temperature was 2500°C and the ablation time was 60s. The smaller the mass ablation rate, the better the ablation resistance of the product.
[0076] The antioxidant properties of the products prepared in Example 1 and Comparative Example 2 were tested by TG-DSC in an air atmosphere, with a heating rate of 10°C / min, a product particle size of 5 μm, and an air atmosphere, and the initial oxidation temperature was read from the DSC heating curve. The higher the initial oxidation temperature, the better the antioxidant properties of the product.
[0077] Table 1
[0078] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A boron- and nitrogen-containing carbide, characterized in that: The molecular formula of the boron- and nitrogen-containing carbide is XC y B z N w ; Wherein, X is at least 4 of Zr, Hf, Ti, Ta, Nb, V, and W, 0.6≤y<1, 0<z≤0.4, 0<w≤0.4, y+z+w≤1; the boron- and nitrogen-containing carbide is a single-phase solid solution having a face-centered cubic structure.
2. The boron- and nitrogen-containing carbide according to claim 1, wherein: X is four or five of Zr, Hf, Ti, Ta, Nb, V, and W.
3. The boron- and nitrogen-containing carbide according to claim 2, wherein: X is Zr, Hf, Ti and Ta, or X is Zr, Hf, Ti, Ta and Nb.
4. The boron- and nitrogen-containing carbide according to claim 1, wherein: 0.75≤y≤0.95, 0.01≤z≤0.15, 0.05≤w≤0.15, y+z+w≤1.
5. The boron- and nitrogen-containing carbide according to claim 1, wherein: The molecular formula of the boron- and nitrogen-containing carbide is (Zr 0.25 Hf 0.25 Ti 0.25 Ta 0.25 )(C 0.82 B 0.10 N 0.08 )、(Zr 0.4 Hf 0.2 Ti 0.2 Ta 0.2 )(C 0.70 B 0.15 N 0.15 )、(Zr 0.2 Hf 0.2 Ti 0.2 Ta 0.2 Nb 0.2 )(C 0.90 B 0.03 N 0.07 )、(Zr 0.3 Hf 0.3 Ti 0.2 Ta 0.1 Nb 0.1 )(C 0.87 B 0.06 N 0.07 ) 6. A method for preparing boron- and nitrogen-containing carbides, characterized in that: The method comprises the following steps: (1) mixing metal powder and carbon powder and grinding them to obtain a mixed powder; wherein the metal powder is at least four selected from the group consisting of Zr powder, Hf powder, Ti powder, Ta powder, Nb powder, V powder, and W powder; (2) subjecting the mixed powder to pressureless spark plasma sintering to obtain carbide powder; (3) Mixing the carbide powder and B2O3 powder under vacuum conditions and then calcining to obtain boron-containing carbide powder; (4) Under vacuum conditions, mixing the boron-containing carbide powder with g-C3N4 powder and subjecting the mixture to high-temperature heat treatment to obtain boron-containing and nitrogen-containing carbides; wherein the temperature of the high-temperature heat treatment is 1500-1800°C; Wherein, the molecular formula of the boron- and nitrogen-containing carbide is XC y B z N w , X is metal, 0.6≤y<1, 0<z≤0.4, 0<w≤0.4, y+z+w≤1.
7. The preparation method according to claim 6, wherein: The metal powder is selected from four or five of Zr powder, Hf powder, Ti powder, Ta powder, Nb powder, V powder and W powder.
8. The preparation method according to claim 7, wherein: The metal powder is Zr powder, Hf powder, Ti powder and Ta powder, or the metal powder is Zr powder, Hf powder, Ti powder, Ta powder and Nb powder.
9. The preparation method according to claim 6, wherein: The grinding is wet ball milling; wherein the operating conditions of the wet ball milling include: a ball milling speed of 150-300 rpm, a ball milling time of 1-5 hours, a ball milling medium of ethanol and / or water, and a ball-to-material ratio of 6-10:
1.
10. The preparation method according to claim 6, wherein: The operating conditions of the pressureless spark plasma sintering include: vacuum degree ≤10Pa, heating rate of 50-150°C / min, temperature of 1300-1800°C, and holding time of 15-60min.
11. The preparation method according to claim 10, wherein: The operating conditions of the pressureless spark plasma sintering include: vacuum degree ≤5Pa, heating rate of 80-120°C / min, temperature of 1500-1700°C, and holding time of 20-40min.
12. The preparation method according to claim 6, wherein: The calcination operation conditions include: vacuum degree ≤ 10Pa, heating rate of 30-150°C / min, temperature of 1400-1900°C, and heat preservation time of 15-60min.
13. The preparation method according to claim 12, wherein: The calcination operation conditions include: vacuum degree ≤ 5 Pa, heating rate of 50-100° C. / min, temperature of 1600-1800° C., and heat preservation time of 20-40 min.
14. The preparation method according to claim 6, wherein: The temperature of the high temperature heat treatment is 1600-1700°C.
15. The preparation method according to claim 14, wherein: The vacuum degree of the high temperature heat treatment is ≤10Pa, preferably ≤5Pa; the heating rate is 30-150°C / min, preferably 50-100°C / min; the insulation time is 15-60min, preferably 20-40min.
Citation Information
Patent Citations
High-entropy boron-containing carbide ultrahigh temperature ceramic powder and preparation method thereof
CN109180188A
Compact and superhard high-entropy boride ceramic as well as preparation method and application thereof
CN110002879A
Cited By
High-conductivity (TiTaNbCrMe) (N, C) high-entropy carbonitride ceramic material and preparation method thereof
CN121470959A